Polyether Ether Ketone Coated with Ultra-Thin Films of Titanium Oxide and Zirconium Oxide Fabricated by DC Magnetron Sputtering for Biomedical Application; Materials; Vol. 15, iss. 22 - Akimchenko I. O. Igor Olegovich; Rutkowski S. Sven; Tran Tuan Hoang; Dubinenko G. E. Gleb Evgenjevich; Petrov V. I. Vsevolod; Kozelskaya A. I. Anna Ivanovna; Tverdokhlebov S. I. Sergei Ivanovich (2022, 2022)
Title screen